Swedish and Portuguese interacting in Swedish MNC's in Portugal: Cultural issues and perspectives - Garrido, Susana Telma (2003)
Genesis: In 1998, Filipe Dahlin from Chalmers University of Technology - Department of Industrial Dynamics (Sweden), presented a thesis with the title 'Swedish Management in Portugal - A Cultural Perspective'. His work was about the interaction between Swedish managers in Portugal (predominantly employed in Swedish Multinational Corporations) and the Portuguese workers in the setting of Organisational life and within the context of a local cultural background. He analysed the different cultural perceptions of Swedish managers in Portugal, particularly, in reference to their Portuguese subordinates. Dahlin's problem was: how well did both cultures "fit" in order to achieve organisational objectives? What adaptations had Swedish managers to engage in order to adapt to the "locals"? How well did the "locals" accepted or engaged in Swedish management practices? However, he only presented and analysed one side of the interaction, namely, the Swedish perspective. In this present work, I took, as the main focus to analyse the Portuguese view on the issues debated by Dahlin. Purpose: Thus, the main reason of this study is to make a complementary analysis to that presented by Dahlin's (1998) work. A sort of symmetrical replication of Dahlin's thesis if you will. The intention is, however, to contribute to the debate of the "Portuguese" type of work ethic, work culture in the frame of the Portuguese difficulty in soaring our productivity level, rather than contributing to some "optimal" model of interaction between Swedes and Portuguese in Swedish Multinational Corporations. Background: The literature on culture and its impacts on organisational life have shown rather well the complexity of the matter. Cultural backgrounds, within which human endeavour takes place, influence management practices and the ways things get done and corporate objectives get attained. When people from significantly different cultural backgrounds interact, the process is not one of mechanical adjustment, and some times it simple does not work. Thus, a qualitative and exploratory study of one of such interactions that has been a success for so long might help to shed some light on the richness and complexity of these processes. Methodology: The methodology followed in this work is similar to that of Filipe Dahlin. A qualitative and exploratory approach sustained by a semi-structured interview process. Some 25 persons were interviewed, amounting to more than 15 hours of recorded conversations. The first step, however, was not to address the Portuguese perspective. As some years passed since Dahlin concluded his work, thus, an intermediate step was taken regarding the evaluation of the degree to which Swedish managers today would or would not agree with the perspective of their former colleagues. Results: The results and outcomes of these interviews are discussed in direct comparison to those put forward by Dahlin, and from that into a more broad discussion around cultural "fits" and to our present national debate on productivity.